Biomimetic cavity-based metal complexes. (16th October 2014) - Rebilly, Jean-Noël; Colasson, Benoit; Bistri, Olivia; Over, Diana; Reinaud, Olivia
Abstract : The biomimetic association of a metal ion with a cavity allows selective recognition, unusual redox properties and new reactivity patterns. Abstract : The design of biomimetic complexes for the modeling of metallo-enzyme active sites is a fruitful strategy for obtaining fundamental information and a better understanding of the molecular mechanisms at work in Nature's chemistry. The classical strategy for modeling metallo-sites relies on the synthesis of metal complexes with polydentate ligands that mimic the coordination environment encountered in the natural systems. However, it is well recognized that metal ion embedment in the proteic cavity has key roles not only in the recognition events but also in generating transient species and directing their reactivity. Hence, this review focuses on an important aspect common to enzymes, which is the presence of a pocket surrounding the metal ion reactive sites. Through selected examples, the following points are stressed: (i) the design of biomimetic cavity-based complexes, (ii) their corresponding host–guest chemistry, with a special focus on problems related to orientation and exchange mechanisms of the ligand within the host, (iii) cavity effects on the metal ion binding properties, including 1st, 2nd, and 3rd coordination spheres and hydrophobic effects and finally (iv) the impact these factors have on the reactivity of embedded metal ions. Important perspectives lie in the use of this knowledge for the development of selective and sensitive probes, new reactions, and green and efficient catalysts with bio-inspired systems.